2002
DOI: 10.1091/mbc.02-01-0601
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of the α6β4 Integrin in Keratinocytes

Abstract: The integrin ␣6␤4 has been implicated in two apparently contrasting processes, i.e., the formation of stable adhesions, and cell migration and invasion. To study the dynamic properties of ␣6␤4 in live cells two different ␤4-chimeras were stably expressed in ␤4-deficient PA-JEB keratinocytes. One chimera consisted of full-length ␤4 fused to EGFP at its carboxy terminus (␤4-EGFP). In a second chimera the extracellular part of ␤4 was replaced by EGFP (EGFP-␤4), thereby rendering it incapable of associating with ␣… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
94
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 102 publications
(106 citation statements)
references
References 55 publications
11
94
1
Order By: Relevance
“…Later on, cells may start to form ␣3␤1-controlled AJs, but they remain mobile, because sheet migration may now dominate. In contrast to ␣3␤1, ␣6␤4 is involved in blocking rather than promoting migration, as previously shown in primary human keratinocytes (10,39), HaCaT cells (6) and in ␤4-deficient PA-JEB keratinocytes, which were rescued by introducing a ␤4 construct (40). Importantly, Geuijen and Sonnenberg (40) showed that ␣6␤4-triggered motility inhibition was not simply due to increased adhesion to Ln-5 but was a result of increased stability of the interaction between ␣6␤4 and Ln-5.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…Later on, cells may start to form ␣3␤1-controlled AJs, but they remain mobile, because sheet migration may now dominate. In contrast to ␣3␤1, ␣6␤4 is involved in blocking rather than promoting migration, as previously shown in primary human keratinocytes (10,39), HaCaT cells (6) and in ␤4-deficient PA-JEB keratinocytes, which were rescued by introducing a ␤4 construct (40). Importantly, Geuijen and Sonnenberg (40) showed that ␣6␤4-triggered motility inhibition was not simply due to increased adhesion to Ln-5 but was a result of increased stability of the interaction between ␣6␤4 and Ln-5.…”
Section: Discussionmentioning
confidence: 83%
“…In contrast to ␣3␤1, ␣6␤4 is involved in blocking rather than promoting migration, as previously shown in primary human keratinocytes (10,39), HaCaT cells (6) and in ␤4-deficient PA-JEB keratinocytes, which were rescued by introducing a ␤4 construct (40). Importantly, Geuijen and Sonnenberg (40) showed that ␣6␤4-triggered motility inhibition was not simply due to increased adhesion to Ln-5 but was a result of increased stability of the interaction between ␣6␤4 and Ln-5. Thus, ␣6␤4-triggered simultaneous up-regulation of both cell-ECM and cell-cell adhesion may result in an adhesive, non-migratory phenotype and may explain the observation that Ln-5 can guide keratinocytes to switch from a migratory-to a dormant, integrated epithelial phenotype (11,41).…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…In vitro cell culture studies have suggested that hemidesmosomes undergo active disassembly and reassembly in response to environmental cues. Time-lapse analysis of the hemidesmosome markers BP180 and b4-integrin has revealed the dynamic properties of these proteins, especially during keratinocyte migration and wound healing in scratch assays (Geuijen and Sonnenberg, 2002;Tsuruta et al, 2003). Moreover, it has been observed that hemidesmosomes get rapidly disassembled during carcinoma invasion (Rabinovitz and Mercurio, 1997;Santoro et al, 2003;Rabinovitz et al, 2004).…”
Section: Initial Hemidesmosome Assemblymentioning
confidence: 99%
“…Although HD provides a stable anchor, its components undergo a rapid turnover, indicating a dynamic equilibrium (12,13). This rapid turnover might allow epithelial cells to efficiently switch between a stationary and a migratory state by quickly changing the balance toward disassembly.…”
mentioning
confidence: 99%